#CoalMustFall: Revisiting Newcastle's coal monument in the Anthropocene. Issue 4 (2nd October 2021) - Cushing, Nancy
Abstract: The recent actions taken against statues of figures associated with colonisation and racial oppression have again drawn attention to the enduring power of monuments in the landscape, even after many have disavowed the values they embody. This article shifts the critique from a focus on race to climate, with an examination of the Jubilee or Coal Monument erected in Newcastle, New South Wales in 1909. This monument was designed with the intention of celebrating coal as the foundation of the city's prosperity and a driver of modernity. In the midst of a climate crisis, its future warrants consideration. Taking an activist stance, it is argued that the monument should be removed to a museum for reframing and reinterpretation while in its place a counter-monument to coal, defined by James E. Young as a 'memorial space conceived to challenge the very premise of the monument', is erected. This counter-monument would serve as a transitional location for expressions of pride in past personal and corporate associations with the coal industry and grief at its passing, while avoiding the creation of an enduring monument which would inevitably become the target of future generations for whom coal will have very different meanings.